Portuguese primary school children’s conceptions about digestion : identification of learning obstacles - Carvalho, Graça Simões de (2004)
A cross-sectional study of Portuguese primary school pupils' conceptions on digestion and the digestive tract was carried out before and after teaching this topic. Pupils of the prior four school years (5/6 to 9/10 year old) drew what happens to a cookie inside their body. In some cases they also wrote a short text or were interviewed. To identify their level of graphic development, they produced a free-hard drawing. The main conceptual changes in explaining digestion were strongly linked to teaching. Children’s previous conceptions were not epistemological obstacles to learning about digestion. The main obstacles were of didactical origin, as images of primary school books do not represent (i) the path of food from the intestine into the blood, (associated to the epistemological obstacle of the permeability of the gut wall); (ii) a clear continuous tract from stomach to anus, which causes a specific confusion at the intestine level.